Penerapan Strategi Pembelajaran Scaffolding Dalam Membentuk Kemandirian Peserta Didik - Adinda Adinda; Sisi Mulia; Irfan Irfan; Gusmaneli Gusmaneli (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The application of problem-based learning strategies with scaffolding aims to help students overcome difficulties in understanding the material according to their level of ability, with the aim of increasing their understanding of the material taught by the teacher. This strategy also aims to stimulate students' creative thinking and create a learning environment that is inclusive, supportive and challenging for students. Learning support provided by teachers can be in the form of instructions, warnings, motivation, dividing problems into steps that are easier to understand, and providing examples according to students' abilities. This research is library research by collecting information from books and journals. This article explains scaffolding strategies and stages in the learning process. From the results of this research, it can be concluded that the scaffolding strategy can be an alternative for educators in building and increasing student learning independence